Reformulation of anti-money laundering policy on crypto assets through the integrated criminal justice system with global regulatory standards - Maulida, Dewi Arum; Na’ima, Vima; Al Azza, Permata (Social, Ecology, Economy for Sustainable Development Goals Journal, 2026)
Background: The emergence of crypto assets as a digital asset has transformed the global financial system, offered innovation but also generated new risks, particularly money laundering (ML). In Indonesia, crypto assets are not recognized as legal tender but has shifted from being classified as a commodity under Commodity Futures Trading Supervisory Agency/Badan Pengawas Perdagangan Berjangka Komoditi (BAPPEBTI) to a digital financial asset under the supervision of Financial Services Authority/Otoritas Jasa Keuangan (OJK) through the enactment of the Law on Development and Strengthening of the Financial Sector/Undang-Undang Pengembangan dan Penguatan Sektor Keuangan (UU P2SK), PP No.49/2024, and POJK No.27/2024. However, the current Anti Money Laundering (AML) framework, especially Law on the Prevention and Eradication of Money Laundering/Undang-Undang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang (UU PPTPPU), has not fully integrated Financial Action Task Force (FATF) recommendations, especially regarding Virtual Assets (VA) and Virtual Asset Service Provider (VASP).  Method: This study employs a doctrinal legal research method utilizing statute, comparative, and conceptual approaches to analyze the reformulation of the Indonesian Anti-Money Laundering Law in alignment with Lawrence Friedman’s legal system theory. The analysis follows a deductive logic by synthesizing primary and secondary legal materials to develop a policy framework that integrates an Integrated Criminal Justice System (ICJS) with machine learning technology for detecting crypto-based money laundering. Finding: Findings reveal that the absence of VA and VASP in Indonesian Anti-Money Laundering Law creates legal gaps that may be exploited by criminals. Reformulation is urgently needed by incorporating VA and VASP definitions, strengthening reporting obligations, and integrating technology such as machine learning in the PPATK’s goAML platform. Conclusion: An Integrated Criminal Justice System (ICJS) model is required to harmonize regulation, institutional coordination, and law enforcement culture. Such a framework is expected to create an adaptive AML system against cryptocurrency-based ML while maintaining financial integrity and supporting sustainable economic development. Novelty/Originality of this article: This research introduces a "techno-legal" transition model for Indonesia’s AML regime, bridging the legislative gap between the new Law on Development and Strengthening of the Financial Sector and the outdated Indonesian Anti-Money Laundering Law.